ZELDOVICH LOCAL PANCAKE: DARK ENERGY DOMINATION - Chernin, A. D.; Karachentsev, I. D.; Emelyanov, N. V. (Одеські астрономічні публікації, 2018)
Zeldovich Local Pancake is a two-dimensional system of 15 giant galaxies nearest to us. Two of the galaxies, the Milky Way and the Andromeda Galaxy, move to each other in the Local Group, while the rest of the galaxies are located around the group at the distances up to 10 Mpc from the group barycenter and move away from it forming a local expansion outﬂow. We use recent Hubble Space Telescope data on local giants and their numerous fainter companions to study the dynamical structure and evolutionary trends of the expanding system. N-body computer model, which reproduces the observed kinematics of the ﬂow, is constructed under the assumption that the system as a whole is embedded in the universal dark energy background. In the model, the motions of the ﬂow bodies are controlled by their mutual attraction force and the repulsion force produced by the dark energy. It is found that the repulsion dominates the force ﬁeld of the system. Because of this, the the system expands with acceleration. The dark energy domination increases with time and introduces to the expansion ﬂow an asymptotically linear velocity-distance relation with the universal time-rate (the Hubble constant) that depends on the dark energy density only